Group of relatives of a psychosocial care center: experiences of the users - Juliane Portella Ribeiro; Valéria Cristina Christello Coimbra; Anelise Miritz Borges (Universidade Federal de Santa Maria, 2012)
Objective: understand the different experiences of the relatives of the person in mental suffering within the family group. Methodology: a qualitative, exploratory and descriptive study, carried out in the domicile of five participants, which are engaged for a minimum period of six months in the Family Group administered by CAPS. The data collection took place in the months of November and December of the year 2009, using semi-structured surveys. Results: the participation of the family in the caring demands their co-responsibility in the formation of connections and in the expression of feelings and doubts among the familial group, building trust to obtain satisfaction with the caring practice. Conclusion: the relatives request the embracement, the listening and the helping to manage the living with the person in mental suffering, optimizing the exchanging and learning of knowledge through the group action